Analisis Tingkat Kebugaran Jasmani Siswa Usia 13 Tahun SMP Al Qolam Muhammadiyah Gemolong Kabupaten Sragen - Syah Fahlefi, Muhammad Reza; Syaukani, Agam Akhmad (Jurnal Porkes, 2025)
This study aims to analyze the level of physical fitness of students at Al Qolam Muhammadiyah Gemolong Junior High School, as well as evaluate the physical condition and factors that influence it. This research is a type of quantitative research with a descriptive approach. The population of this study included all students aged 13 years, with a total of 90 students. Given the relatively small population, this study used total sampling technique. The analysis technique in this study is descriptive quantitative. The instrument used in the study was the Nusantara Student Fitness Test. The results showed an average student physical fitness score of 1.83, which is included in the deficient category. The measurements indicated that many students had difficulties in terms of endurance and flexibility, although some of them had good nutritional status. The findings emphasize the need for planned physical education interventions, improved sports facilities, and attention to diet and stress management. In terms of research novelty, this study provides insights into students' physical fitness levels using the TKPN instrument developed by the Ministry of Youth and Sports. The use of TKPN allows for a more standardized assessment of fitness and can be compared with National data.